Early Trypanosoma cruzi Infection Triggers mTORC1-Mediated Respiration Increase and Mitochondrial Biogenesis in Human Primary Cardiomyocytes - Libisch, M. Gabriela; Faral-Tello, Paula; Garg, Nisha J.; Radi, Rafael; Piacenza, Lucía; Robello, Carlos (Frontiers in Microbiology, 2018)
Chagasic chronic cardiomyopathy is one of the most frequent and severe manifestations of Chagas disease, caused by the parasite Trypanosoma cruzi. The pathogenic and biochemical mechanisms responsible for cardiac lesions remain not completely understood, although it is clear that hypertrophy and subsequent heart dilatation is in part caused by the direct infection of cardiomyocytes. In this work, we evaluated the initial response of human cardiomyocytes to T. cruzi infection by transcriptomic profiling. Immediately after infection, cardiomyocytes dramatically change their gene expression patterns, up regulating most of the genes encoding for respiratory chain, oxidative phosphorylation and protein synthesis. We found that these changes correlate with an increase in basal and maximal respiration, as well as in spare respiratory capacity, which is accompanied by mitochondrial biogenesis pgc-1α independent. We also demonstrate that these changes are mediated by mTORC1 and reversed by rapamycin, resembling the molecular mechanisms described for the non-chagasic hypertrophic cardiomyopathy. The results of the present work identify that early during infection, the activation of mTORC1, mitochondrial biogenesis and improvement in oxidative phosphorylation are key biochemical changes that provide new insights into the host response to parasite infection and the pathogenesis of chronic chagasic cardiomyopathy. The finding that this phenotype can be reversed opens a new perspective in the treatment of Chagas disease, through the identification of host targets, and the use of combined parasite and host targeted therapies, in order to prevent chagasic cardiomyopathy.